Factores socio afectivos asociados a la producción de textos escritos en inglés en estudiantes de quinto grado de secundaria en instituciones educativas públicas de Iquitos 2021 - Soria Filomeno, Sergio Eliseo (2023)
The objective of this study was to explain the influence of socio affective factors in fifth year students’ English writing skills at public high schools in Iquitos district 2021. The research type was explanatory with field study, contemporary transectional, and multivariate designs. The study population was made up by 2697 students and a stratified sample with proportional allocation of 329. Results show that the mean score in English writing was 10,09 out of 20, which is categorized as beginner, as well as in its dimensions: Adaptation to the communicative situation (10.11), text organization and development (9.93), use of written language conventions (10.122), reflection and evaluation of the text format, content and context (10.19). Results in the socio-affective factors variable show that the mean score was 50.33 out of 100. The correlation index was r= -0.025. In conclusion, results of the nonparametric Spearman's Rho test show that there is no correlation between the study variables since the correlation is negative and the p-value = 0.326 > α = 0.05, therefore, the binary regression test was not applied to this study; hence there is no influence of socio-affective factors into English writing, rejecting the research hypothesis.